1995
DOI: 10.1002/pro.5560041012
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing loop swaps in the CDRs of an immunoglobulin VL domain

Abstract: It is generally believed that loop regions in globular proteins, and particularly hypervariable loops in immunoglobulins, can accommodate a wide variety of sequence changes without jeopardizing protein structure or stability. We show here, however, that novel sequences introduced within complementarity determining regions (CDRs) 1 and 3 of the immunoglobulin variable domain REI VL can significantly diminish the stability of the native state of this protein. Besides their implications for the general role of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Most substitutions are not tolerated, suggesting that sequence information in this turn plays a significant role in dictating the overall structure of the 0-barrel. These results are consistent with recent work by Helms and Wetzel(1995), who reported that substitutions in the hypervariable loops of an immunoglobulin V, domain destabilize the structure of that P-barrel as well. Mutagenesis studies of a &turn in staphylococcal nuclease have led to similar conclusions (R.O.…”
Section: Ja Ybe and Mh Hechtsupporting
confidence: 93%
“…Most substitutions are not tolerated, suggesting that sequence information in this turn plays a significant role in dictating the overall structure of the 0-barrel. These results are consistent with recent work by Helms and Wetzel(1995), who reported that substitutions in the hypervariable loops of an immunoglobulin V, domain destabilize the structure of that P-barrel as well. Mutagenesis studies of a &turn in staphylococcal nuclease have led to similar conclusions (R.O.…”
Section: Ja Ybe and Mh Hechtsupporting
confidence: 93%
“…4). Destabilizing effects of loop grafting into an antibody framework have been reported previously (40), but in that particular case, the grafted sequences were totally unrelated to antibody hypervariable loops. The use of naturally occurring CDR sequences for grafting into immunoglobulin frameworks often ensures that the inserted loops are optimally functional as they have been proofread and selected for functionality during the formation of the B cell receptors.…”
Section: Discussionmentioning
confidence: 67%
“…Apparent differences may be due to the nature of CDR loops that are, by necessity, different in all V L domains. A systematic study of the contribution of different CDR loops has not been carried out; however, significant differences in the stability of isolated V L domains have been observed with different length loops, 76 and replacement of the loops in one V L domain has significantly increased stability. 77 Loop regions can be important in the initial stages of protein folding, bringing different regions of the protein into close proximity.…”
Section: Comparison To Other Ig-like Domainsmentioning
confidence: 96%